Impact of integration of renewable energies and energy efficiency on the reliability of the national electricity grid - Karmich, Saida; Ziani, El Mostafa; Bouchnaif, Jamal; El Malki, Mohamed (International Journal of Power Electronics and Drive Systems (IJPEDS), 2023)
This article consists of studying the reliability of the Moroccan electricity grid as well as verifying the plan of production for 2030. To propose an adequate production plan for 2050, a production plan where renewable energies take a large place in the production park. Our objective is the planning and optimization of the Moroccan energy system with a strong integration of renewable energy sources or even 100% integration by guaranteeing the reliability of the electrical system. In this study, we evaluated the reliability of the Moroccan electricity grid in the presence of renewable electricity production based on the energy plan simulator supplemented by Monte Carlo simulations based on probabilistic approaches. The first part of this work consists of projecting demand for 2030-2050 and studying the impact of energy efficiency on forecasts. In the second part, we integrated the existing means of production and the projected demand on energy plan. In the third part we studied the reliability of the Moroccan electricity grid in the presence of the production of wind, solar photovoltaic (PV) and concentrated solar (CSP) electricity according to different stages of study (from 2017 to 2050).